The Effect Of Using Example Non Example Method Toward Students' Writing Ability in Narrative Text at The Tenth Grade Students of SMA N 3 Mandau - Kamini Saputri Wulva (Jolly Journal of English Education, 2025)
This study dealt with the effect of using example non example method toward students’ writing ability in narrative text at the tenth grade students of SMA N 3 Mandau. The purpose of this study was to determine the significant effect of using example non example method students writing ability in narrative text. The researcher use quasi- experimental research design with quantitative approach. The population of the research was the students at the tenth grade students of SMA N 3 Mandau which has 429 students consists of twelve classes. Two classes, X1 and X5, with a combined student body of 72, were used as samples by the researcher. One class served as an experimental class that received treatment, while the other class served as a control class that did not receive treatment. The students were selected by using cluster random sampling. One method of gathering data was by using a written exam. The independent sample t-test from SPSS 22 shows that there was a significant difference in the writing skills of the students in the post-test experiment class compared to the post-test control class, it showed that sig. (2-tailed) was smaller than 0.05 (0.000 < 0.05). t mean there was significant difference on studnets’ writing ability between experiment class by using Example non Example Method and control class without using Example non Example Method.